The Bangsamoro armed resistance in southern Philippines : the role of Shaykh Salamat Hashim and his views on peace and war in islam - Abdul M. Lantong (International Institute of Islamic Thought and Civilization, International Islamic University Malaysia, 2015)
Using the framework of Islamic doctrine of peace and war, this study examines and analyzes the role of Shaykh Salamat Hashim in the Bangsamoro armed resistance in Southern Philippines as well as the significance of his views on peace and war in Islam. Understanding these issues is of paramount significance in understanding the nature and course of the Bangsamoro armed resistance movement. Shaykh Salamat Hashim played vital roles in the present Bangsamoro armed resistance in Southern Philippines. He was the founding leader, amir and ideologue of the armed resistance movement. In these capacities, Shaykh Salamat Hashim was able to transform the resistance movement so that it was not only an armed revolutionary organization, but also a vehicle and vanguard of Islamic revivalism in the area by formulating its Islamic ideological foundations, agenda and methodology based on the Qur'an and Sunnah (Traditions) of Prophet Muhammad. As an Islamic scholar, Shaykh Salamat Hashim viewed peaceful means, not war, as the primary basis of policy in resolving the Moro-Filipino conflict. For him, war comes as a last resort in achieving the objectives of eliminating injustice, oppression and aggression in the Bangsamoro society. Viewed in this context, the chance of peaceful resolution of the Moro-Filipino conflict is within reach. Consistently with this view, however, a peaceful and negotiated political solution must necessarily be based on justice, equality and mutual respect. The data gathered are based on primary sources such as the khutbah(s) (religious sermons), speeches, lectures, press releases and interviews of Shaykh Salamat Hashim. These data are supplemented by the results of key informant interviews (KII) and the articles written about him.